ISLAM DAN HUBUNGAN ANTAR AGAMA - Sulaiman Mohammad Nur (Program Studi Studi Agama Agama Fakultas Ushuluddin dan Pemikiran Islam, 2018)
The existence of the world is accompanied by the reality of various religions, languages, and cultures. Various conflicts that arise in the world actually arise from the lack of understanding of this diversity which even appears in the form of violence in the name of religion. In the confusion caused by conflict about diversity, pluralism was born as a solution.. But of course, because pluralism comes from outside Islam, it is necessary to do an in-depth study of whether this flow is in line with the spirit of Islam or vice versa. The results of the study on this matter are that Islam accepts pluralism. Some points to be argued in this case are the equality of divine religions in tauhid uluhiyah faith, Islam teaches tolerance both among religious people and among religious believers, and even Islam teaches the teachings of brotherhood not only in the form of ukhuwwah Islamiyah but also in ukhuwwah insaniyyah. Even so, Islam does not accept pluralism in the concept of John Hick who believes that all religions are true and leads to salvation, because what is meant by Islam with pluralism is a peaceful social life between humans with different religious understanding. Theological differences are indeed undeniable in their existence in religious life. But Islam is a religion that is best prepared to interact with other religions in social matters, both in concept and in application.